Business intelligence and big data : drivers of organizational success - Olszak, Celina (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Thetwenty-first century is a time of intensifying competition and progressive digitization. Individual employees, managers, and entire organizations are under increasing pressure to succeed. The questions facing us today are: What does success mean? Is success a matter of chance and luck or perhaps is success a category that can be planned and properly supported? Business Intelligence and Big Data: Drivers of Organizational Success examines how the success of an organization largely depends on the ability to anticipate and quickly respond to challenges from the market, customers, and other stakeholders. Success is also associated with the potential to process and analyze a variety of information and the means to use modern information and communication technologies (ICTs). Success also requires creative behaviors and organizational cleverness from an organization. The book discusses business intelligence (BI) and Big Data (BD) issues in the context of modern management paradigms and organizational success. It presents a theoretically and empirically grounded investigation into BI and BD application in organizations and examines such issues as: Analysis and interpretation of the essence of BI and BD Decision support Potential areas of BI and BD utilization in organizations Factors determining success with using BI and BD The role of BI and BD in value creation for organizations Identifying barriers and constraints related to BI and BD design and implementation The book presents arguments and evidence confirming that BI and BD may be a trigger for making more effective decisions, improving business processes and business performance, and creating new business. The book proposes a comprehensive framework on how to design and use BI and BD to provide organizational success.
1. Changing Business Environments and Decision Support Systems. 2. Business Intelligence in Management of Organizations. 3. Big Data for Business Intelligence. 4. Analysis of Business Intelligence and Big Data Adoption in Organizations. 5. Measurement and Assessment of Business Intelligence and Big Data Development in Organizations.
"An Auerbach book."
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Database Management / Data Mining; BUSINESS & ECONOMICS / Management Science; COMPUTERS / Information Technology; Business intelligence; Big data